Simplify (2xy^2+3)((2xy^2)^2-(2xy^2)(3)+(3)^2) This reminds me of (U+a)(U^2- aU + a^2). When mulipltiplied out, one gets a cubic equation. Do you remember the formula for factoring the sum of two cubes?
Can 2xy - y - 1 be factored out? How? about all you can do is take the common y out of the first two terms; that in itself is not much help. dont know if this is rite or not..but just a guess.. assuming 2xy - y - 1 = 0 2xy - y = 1
Consider the equation: x^2 - 2xy + 4y^2 = 64 Write an expression of the slope of the curve at any point. (y^p)= y prime My work 2x - 2(xy^p + y) + 8yy^p = 0 2x -2xy^p - 2y + 8yy^p = 0 -2xy^p + 8yy^p = 2y -2x factored out y^p and then …
I thought number 4 on this list was incorrect but didn't know how to fully explain it here is the list that I have. Please look at the following simplification of an algebraic expression. Which line contains the mistake and why?
find the equation of all horizontal tangents to the curve y^2 = (x^2+4)/x, if any exist this is what I have so far: xy^2= x^2+4 2xydy/dx = 2x-y^2 dy/dx = (2x-y^2)/2xy (2x-Y^2)/2xy = 0 2x- Y^2 = 0 I don't know what to do after this